When the Shadow Is the Substance: Judge Gender and the Outcomes of Workplace Sex Discrimination Cases - Knepper, Matthew (Journal of Labor Economics, 2018)
The number of workplace sex discrimination charges filed with the Equal Employment Opportunity Commission approaches 25,000 annually. Do the subsequent judicial proceedings suffer from a discriminatory gender bias? Exploiting random assignment of federal district court judges to civil cases, I find that female plaintiffs filing workplace sex discrimination claims are substantially more likely to settle and win compensation whenever a female judge is assigned to the case. Additionally, female judges are 15 percentage points less likely than male judges to grant motions filed by defendants, which suggests that final negotiations are shaped by the emergence of the bias.